Kajian Variasi Perkuatan Elemen Struktur Balok Dengan Steel Solid Plate, Jacketing, dan Carbon Fiber Reinforcement Polymer (CFRP) Terhadap Ketahanan Lentur - Rahmadi, Gandung; Ferdika, Ferdika; Fauzan (Dept. of Civil Engineering Universitas Riau, 2024)
The collapse of concrete structures due to excessive loads is a serious issue that can lead to significant losses, both in terms of materials and human safety. This phenomenon is often caused by a weak understanding of the load mechanism acting on structural elements, including the interaction behavior between reinforcing steel and concrete. In both new and old buildings, damage to certain structural elements, especially beams, is inevitable. This damage occurs due to design errors in the building, mistakes during construction execution, or changes in the building's function. With the advancement of technology, there are now reinforcement methods for beam structural elements, including Steel Solid Plate, Jacketing, and Carbon Fiber Reinforcement Polymer (CFRP). These three methods will be evaluated based on deflection and strength.